2018
DOI: 10.3390/molecules23092167
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols from Acorn Leaves (Quercus liaotungensis) Protect Pancreatic Beta Cells and Their Inhibitory Activity against α-Glucosidase and Protein Tyrosine Phosphatase 1B

Abstract: Acorn leaves, which possess potential pharmacologic effects, are traditionally consumed as food in China. Phytochemical investigations of acorn leaves yielded one new and 25 known polyphenols, and their structures were identified by extensive spectroscopic analysis. Three antidiabetes assays were conducted. Compound 2 considerably increased the survival of pancreatic beta cells by reducing the production of reactive oxygen species and enhancing the activities of superoxide dismutase, catalase, and glutathione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…In both cases, the inhibitory effect was concentration-dependent. The inhibitory activity against PTP-1B reported for compounds 4 and 6 correlated well with that found in this work [19,20]. On the other hand, rosmarinic acid (5) is an ingredient of an active extract of Rosmarinus officinalis against PTP-1B [21].…”
Section: Evaluation Of Compounds 1-8ab On the Ptp-1b Inhibitory Actisupporting
confidence: 86%
“…In both cases, the inhibitory effect was concentration-dependent. The inhibitory activity against PTP-1B reported for compounds 4 and 6 correlated well with that found in this work [19,20]. On the other hand, rosmarinic acid (5) is an ingredient of an active extract of Rosmarinus officinalis against PTP-1B [21].…”
Section: Evaluation Of Compounds 1-8ab On the Ptp-1b Inhibitory Actisupporting
confidence: 86%
“…e authors found that all the compounds showed strong inhibitory effects on PTP1B and α-glucosidase, but inhibition of α-amylase was not observed [87]. It was also reported that the polyphenol fraction from acorn leaves (Quercus liaotungensis) inhibited α-glucosidase and PTP1B activity [49].…”
Section: Antidiabetic Effectmentioning
confidence: 98%
“…Flavonoids are also found to be important bioactive compounds of Quercus leaves. Xu et al [87] conducted a study on acorn leaves (Quercus liaotungensis) and isolated one new flavonoid glycoside, namely, 2,3-diol acetonide-3-O-α-L-rhamnopyranoside-kaempferol, and 25 known polyphenolics. Recently, a study carried out on the infusion of the leaves of the six different species of Quercus revealed the presence of 7 flavan-3-ols, 2 flavonols, 18 flavonols/flavanone glycosides, 1 flavanone, 1 flavone, and 4 other unknown compounds.…”
Section: Phytochemicalsmentioning
confidence: 99%
“… 28 Quercetin, kaempferol and myricetin showed the potent PTPN1 inhibitory activity as sodium orthovanadate, a phosphatase inhibitor. 29 PTPN1 inhibitory activity was increased by the degree of polymerization of proanthocyanidins. 30 CoLE contained flavonoids, flavonoid glycosides and proanthocyanidins.…”
Section: Resultsmentioning
confidence: 97%
“… 13 These compounds were reported to have PTPN1 and α-glucosidase inhibitory activities. 29 The above-mentioned studies revealed that CoLE could alleviate the symptoms of diabetes by inhibiting activity of PTPases on liver, muscle and epididymal fat. The high AUC of OGTT and FBG of hyperglycemic rats are ameliorated by CoLE treatments.…”
Section: Resultsmentioning
confidence: 98%